Clinical utility of circulating calprotectin to assist prediction and monitoring of COVID‐19 severity: An Italian study. Issue 12 (17th August 2022) - Infantino, Maria; Manfredi, Mariangela; Alessio, Maria Grazia; Previtali, Giulia; Grossi, Valentina; Benucci, Maurizio; Faraone, Antonio; Fortini, Alberto; Grifoni, Elisa; Masotti, Luca; Russo, Edda; Amedei, Amedeo; et al.
Abstract: Background: Calprotectin (S100A8/A9) has been identified as a biomarker that can aid in predicting the severity of disease in COVID‐19 patients. This study aims to evaluate the correlation between levels of circulating calprotectin (cCP) and the severity of COVID‐19. Methods: Sera from 245 COVID‐19 patients and 110 apparently healthy individuals were tested for calprotectin levels using a chemiluminescent immunoassay (Inova Diagnostics). Intensive care unit (ICU) admission and type of respiratory support administered were used as indicators of disease severity, and their correlation with calprotectin levels was assessed. Results: Samples from patients in the ICU had a median calprotectin concentration of 11.6 µg/ml as compared to 3.5 µg/ml from COVID‐19 patients who were not in the ICU. The median calprotectin concentration in a cohort of healthy individuals collected before the COVID‐19 pandemic was 3.0 µg/ml (95% CI: 2.820–2.969 µg/ml). Patients requiring a Venturi mask, continuous positive airway pressure, or orotracheal intubation all had significantly higher values of calprotectin than controls, with the increase of cCP levels proportional to the increasing need of respiratory support. Conclusion: Calprotectin levels in serum correlate well with disease severity and represent a promising serological biomarker for the risk assessment of COVID‐19 patients.